Propensity‐score‐matched comparative analyses of simultaneously administered fixed‐ratio insulin glargine 100 U and lixisenatide (iGlarLixi) vs sequential administration of insulin glargine and lixisenatide in uncontrolled type 2 diabetes - Rosenstock, Julio (Diabetes Obes Metab, 2018)
AIM: To conduct two exploratory analyses to compare indirectly the efficacy and safety of simultaneous administration of insulin glargine 100 U (iGlar) and the glucagon‐like peptide‐1 receptor agonist (GLP‐1RA) lixisenatide (Lixi) as a single‐pen, titratable, fixed‐ratio combination (iGlarLixi [LixiLan trials]) vs sequential administration of iGlar + Lixi (GetGoal Duo trials) in people with type 2 diabetes (T2D). MATERIALS AND METHODS: Propensity‐score matching based on baseline covariates was used to compare simultaneous iGlarLixi vs sequential combination of iGlar + Lixi with the addition of Lixi in patients who did not reach the glycated haemoglobin (HbA1c) goal of <53 mmol/mol (<7%) after short‐term use of iGlar alone (LixiLan‐O vs GetGoal Duo‐1 comparison) and vs sequential addition of Lixi in uncontrolled patients after long‐term use of iGlar alone (LixiLan‐L vs GetGoal Duo‐2 comparison). RESULTS: In both analyses, compared with sequential iGlar + Lixi, iGlarLixi led to significantly greater HbA1c reductions with associated weight loss and significantly more patients reaching target HbA1c <53 mmol/mol despite lower insulin doses. Symptomatic hypoglycaemia rates were similar, despite greater HbA1c reductions with iGlarLixi. Lower rates of gastrointestinal adverse events were observed with iGlarLixi, probably as a result of the more gradual titration of Lixi with iGlarLixi. CONCLUSIONS: Indirect propensity‐score‐matched exploratory comparisons suggest that early treatment with a simultaneous, titratable, fixed‐ratio combination of basal insulin and a GLP‐1RA (iGlarLixi) may be more effective and possess better gastrointestinal tolerability than a sequential approach of adding a GLP‐1RA in patients with uncontrolled T2D initiating or intensifying basal insulin therapy.